Construction of a mobile application as a strategy for medication adherence in the elderly population - Larissa Pereira da Silva; Francisco Ayslan Ferreira Torres; Antonio José Silva dos Santos; Luciano Gualberto Soares; Adriana de Moraes Bezerra; Maria Naiane Rolim Nascimento (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2023)
Objective: To describe the process of developing an application as a strategy to promote medication adherence in the elderly population. Methods: Methodological research of technological production. The steps of data survey, database assembly and software development were followed. A narrative review of the literature on the theme was performed. Results: In order to develop the technological tool, a prototype of the application was initially made. The central objective was to create an application program to remember the medication schedule through sound warnings and on-screen information, focusing on the autonomy of the health-disease process of the elderly population, using an accessible language, with large and legible fonts, with specific colors for the background screen and Ooblets suitable for the understanding of the target audience. Conclusion: The application contributes to medication adherence by the elderly patients, in addition to helping caregivers regarding the correct use, appropriate time, and correct dosage. The proposed technology provides the co-responsibility of the elderly citizens in their health-disease process and adherence to the prescribed therapy.